Not in our community: Queer women challenge religious homophobia in rural Kentucky. Issue 3 (2nd July 2020) - Barton, Bernadette; Currier, Ashley
Abstract: "Not in my backyard" (NIMBY) movements emerge when a social or political event spurs opposition from local residents. Much research on NIMBY movements concentrates on local residents' efforts to defend their community from unwanted "outsiders" or elements, such as a waste incinerator or sex offenders. Little is written on how NIMBY activism can redefine a place to be more inclusive of sexual minorities and supportive of progressive social initiatives. After the Supreme Court's 2015 ruling in favor of marriage equality in Obergefell v. Hodges, Rowan County Clerk Kim Davis refused to issue marriage licenses to same-sex couples citing her religious beliefs. Davis' actions galvanized marriage-equality and religious-freedom activists in the region. Pro-marriage-equality activists included lesbian, bisexual, pansexual, and queer women who viewed Davis' action as an attack on their legitimacy in the community. Drawing on 11 interviews with queer women in Kentucky, we explore how their activist work in Rowan County challenged small-town intolerance and religious homophobia and helped to re-form the region as more a progressive space for sexual minorities.